HERPETIC INFECTION OF THE FIRST TYPE IN THE ORAL MUCOSA AND FACIAL SKIN: MODERN TREATMENT GUIDELINES - Ischeykin, K.; Skripnikova, T.; Pavlenko, L.; Bilokon, S. (World of Medicine and Biology, 2012)
Based on the results of own research and observations, given the published data, the authors proposed a pathogenetically based, differentiated schemes of treatment of herpeticlesions of the oral mucosa and skin, depending on the nosological form of the diseases’ stage and patient age.